2011
DOI: 10.1111/j.1365-4632.2010.04677.x
|View full text |Cite
|
Sign up to set email alerts
|

Androgenetic alopecia and insulin resistance: are they truly associated?

Abstract: Patients with metabolic syndrome, with or without AGA, were significantly more insulin resistant compared with patients with AGA with no metabolic syndrome and with healthy subjects and, therefore, no true association exists between AGA and insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
3
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 22 publications
2
20
3
7
Order By: Relevance
“…The Finnish study reported the same region with the previous study the prevalence rates of impaired glucose regulation and insulin resistance were found to be significantly higher among the women with hair loss compared to women with normal hair [10]. However, on contrary these studies in case controlled study from Egypt no association was observed between AGA and insulin resistance in young aged group including both gender [11]. In relation to this study in Nabaie et al study there was no difference in individual components of metabolic syndrome including serum fasting insulin level, fasting blood glucose, serum total cholesterol, triglyceride, high density cholesterol levels (HDL-C) and insulin resistance between the AGA and a control group [12].…”
contrasting
confidence: 37%
“…The Finnish study reported the same region with the previous study the prevalence rates of impaired glucose regulation and insulin resistance were found to be significantly higher among the women with hair loss compared to women with normal hair [10]. However, on contrary these studies in case controlled study from Egypt no association was observed between AGA and insulin resistance in young aged group including both gender [11]. In relation to this study in Nabaie et al study there was no difference in individual components of metabolic syndrome including serum fasting insulin level, fasting blood glucose, serum total cholesterol, triglyceride, high density cholesterol levels (HDL-C) and insulin resistance between the AGA and a control group [12].…”
contrasting
confidence: 37%
“…Fifty seven males aged 19-30 years presenting with patterned hair loss (defined as grade 3 or more on the alopecia classification scale of Hamilton with Norwood modification) were taken as study subjects [5,6]. Thirty two age matched males with no evidence of hair loss were taken as controls.…”
Section: Methodsmentioning
confidence: 99%
“…[910] The association between AGA and MetS may be gender-specific to females. [11] Furthermore, the association of MetS with increasing severity of AGA is inconclusive.…”
Section: Introductionmentioning
confidence: 99%